(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
Objective: Present study analyzed retrospectively the complications associated with one stage sequential bilateral Total Knee Arthroplasty. Methods: A total of 107 bilateral knee osteoarthritis (OA) patients who underwent one stage sequential bilateral primary total knee replacement were included in this retrospective study. All the patients included were classified as American Society of Anaesthesiology (ASA) 1 or 2 with a pre operative Haemoglobin of 12gm/dl & were operated upon by the same surgeon. After six months follow up of patients were conducted and following parameters were recorded: the perioperative complications, mean operative time for knees and mean hospital stay. Results: Three cases of deep vein thrombosis, two cases of post op delirium and superficial infection and one case each of myocardial infarction, suspected pulmonary embolism and cardiac dysrhythmia were reported but there were no perioperative deaths, neurological complications or revision procedures. Mean operative time was 143±10.27 min. Mean hospital stay was 4.6±0.94 days. The results were statistically significant (p<0.05). Conclusion: Patients undergoing one stage sequential bilateral TKA tend to show better results due to shorter hospital stay, shorter operative time, faster recovery and early rehabilitation as well as with fewer complications depending on careful patient selection.